LOCAL COUNCIL EMPLOYEES’ INTEGRITY: A CASE STUDY OF ENFORCEMENT AND LICENSING DEPARTMENT - Shahriza Ilyana Ramli; Anis Nur Najwa Adam; Nursyakirah Shamsudin; Nor Zaini Zainal Abidin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The integrity and governance of public servants remain an ongoing concern. Despite numerous efforts to curb corruption and uphold integrity in the public sector, recent trends indicate a surge in misconduct among civil servants, particularly instances of corruption. This study aims to investigate the key factors—accountability, risk management, and managerial commitment—that significantly impact the integrity of civil servants within the Enforcement and Licensing Department of a municipal council in Perak. Employing a census sampling method, this research collected primary data from 101 civil servants within the department. Among the three independent variables examined, accountability emerges as the most influential factor shaping the integrity of civil servants in the Enforcement and Licensing Department. The choice to focus on a municipal council stems from documented cases of corruption involving civil servants within such councils. Thus, this study seeks to investigate integrity levels at the chosen municipal council, shedding light on the integrity of civil servants in this context.